The role and challenges of intratumoral microbiota in colorectal cancer immunotherapy - Hao, Miao; Xu, Haiming; Li, Min; Jiao, Dan (Frontiers in Pharmacology, 2025)
Colorectal cancer (CRC) is the third most common malignant tumor globally, and its development is closely related to interactions between the host and microbes. Recent studies have shown that the diversity of intratumoral microbiota significantly influences CRC progression and responses to immune therapy. This influence occurs through mechanisms such as immune microenvironment regulation, metabolic reprogramming, and epigenetic modifications. However, there is still a lack of systematic analysis regarding the diversity of intratumoral microbiota in CRC and its immune regulatory mechanisms, particularly in the metabolic and immune regulation. This article presents a systematic review of the compositional characteristics of intratumoral microbiota in CRC, the associated immune regulatory mechanisms, and their roles in chemotherapy and immunotherapy. It also discusses challenges like standardizing microbiome detection methods and the ethics of clinical translation, while proposing a strategy for integrating multi-omics using artificial intelligence. This article provides a theoretical basis for developing personalized treatment regimens that target the microbiota.